(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
A novel from the Border. After the publication of Responso por un bandolero (LOM, 1997), generously received by the public and critics, Enrique Volpe once again takes the historical reference for the elaboration of, his second novel: A Captain Gallops on the Borders of Hell. The novel is based on the legendary life of a character in Chilean history, sadly famous for the cruelty of his crimes as a member of the Border Police Force: Captain Hernán Trizano.